The value of the Hubble–Lemaître constant queried by Type Ia supernovae: a journey from the Calán-Tololo Project to the Carnegie Supernova Program. Issue 1 (29th October 2020) - Hamuy, Mario; Cartier, Régis; Contreras, Carlos; Suntzeff, Nicholas B
ABSTRACT: We assess the robustness of the two highest rungs of the 'cosmic distance ladder' for Type Ia supernovae and the determination of the Hubble–Lemaître constant. In this analysis, we hold fixed Rung 1 as the distance to the LMC determined to 1 per cent using detached eclipsing binary stars. For Rung 2, we analyse two methods, the TRGB and Cepheid distances for the luminosity calibration of Type Ia supernovae in nearby galaxies. For Rung 3, we analyse various modern digital supernova samples in the Hubble flow, such as the Calán-Tololo, CfA, CSP, and Supercal data sets. This metadata analysis demonstrates that the TRGB calibration yields smaller H 0 values than the Cepheid calibration, a direct consequence of the systematic difference in the distance moduli calibrated from these two methods. Selecting the three most independent possible methodologies/bandpasses ( B, V, J ), we obtain H 0 = 69.9 ± 0.8 and H 0 = 73.5 ± 0.7 km s^-1 Mpc^-1 from the TRGB and Cepheid calibrations, respectively. Adding in quadrature the systematic uncertainty in the TRGB and Cepheid methods of 1.1 and 1.0 km s^-1 Mpc^-1, respectively, this subset reveals a significant 2.0 σ systematic difference in the calibration of Rung 2. If Rung 1 and Rung 2 are held fixed, the different formalisms developed for standardizing the supernova peak magnitudes yield consistent results, with a standard deviation of 1.5 km s^-1 Mpc^-1, that is, Type Ia supernovae are able to anchor Rung 3 with 2 per cent precision. This study demonstrates that Type Ia supernovae have provided a remarkably robust calibration of R3 for over 25 yr.